Verdant Treasures: Unveiling the Ecological Distribution, Conservation Status, and Medicinal Marvels of Pogonatum species in India-A Holistic Review - Vayalil, Sarath Ramesan Velu; Nair, Swathi Sasidharan; Sarayu, Manoj Gopal (Asian Journal of Biological and Life Sciences)
Pogonatum moss is a fascinating plant that has garnered a lot of attention because of its wide range of biological distribution, potential medical benefits, and conservation implications. This thorough analysis explores the complex story of Pogonatum moss, explaining its widespread distribution, state of conservation, and extraordinary therapeutic potential. The review synthesizes a plethora of scientific knowledge and highlights the importance of Pogonatum in ecological and biomedical domains, urging more study and conservation efforts.
Keywords: Pogonatum; Geographical distribution; Conservation status; Medicinal properties